The law of class actions in Canada - Winkler, Warren K. (Canada Law Book, 2014)
"Class actions are increasingly playing a significant role in providing access to justice to people who have experienced a common wrong. The volume of class actions jurisprudence in Canada has increased exponentially in recent years. Containing insights from two of the foremost Canadian class action jurists and a leading academic in the field, this text offers a comprehensive review of the ever-expanding law of class actions from trial and appellate courts across Canada"--Publisher.